Cerebellar damage impairs the self-rating of regret feeling in a gambling task - Clausi, Silvia; Coricelli, Giorgio; Pisotta, Iolanda; Pavone, Enea Francesco; Lauriola, Marco; Molinari, Marco; Leggio, Maria (Frontiers in Behavioral Neuroscience, 2015)
Anatomical, clinical, and neuroimaging evidence implicates the cerebellum in processing emotions and feelings. Moreover recent studies showed a cerebellar involvement in pathologies such as autism, schizophrenia and alexithymia, in which emotional processing have been found altered. However, cerebellar function in the modulation of emotional responses remains debated. In this study, emotions that are involved directly in decision-making were examined in 15 patients (six males; age range 17-60 years) affected by cerebellar damage and 15 well matched healthy controls. We used a gambling task, in which subjects’ choices and evaluation of outcomes with regard to their anticipated and actual emotional impact were analyzed. Emotions, such as regret and relief, were elicited, based on the outcome of the unselected gamble. Interestingly, despite their ability to avoid regret in subsequent choices, patients affected by cerebellar lesions were significantly impaired in evaluating the feeling of regret subjectively. These results demonstrate that the cerebellum is involved in conscious recognizing of negative feelings caused by the sense of self-responsibility for an incorrect decision.